The structure of prosocial behavior. Its approach through the Multidimensional Item Response Theory’s two-factor model - Auné, Sofía Esmeralda (2019)
Problem and objectives: To find out if the structure of the prosocial behavior measured by the Prosocial Behavior Scale (PBS) can be represented by a general factor, i.e. prosociality, combined with specific factors: the subscales of the PBS. Method: The sample consisted of 692 subjects (65% females) recruited by a convenience sampling method and living in Greater Buenos Aires and inland areas of Argentina. The assumptions of unidimensionality and local dependence were checked. Then the relative fit was compared between three models of the Item Response Theory: Graded Response Model (GRM), Multidimensional Graded Response Model (MGRM) and Two-Factor Graded Response Model (TGRM). Results: The TGRM showed the best relative fit. This model was implemented by calculating the conditional and marginal parameters. Likewise, the ECV index was calculated. Conclusions: The PBS items were primarily influenced by prosociality. The Help subscale explained a significant proportion of the common variance. In contrast, the Comfort subscale, considered as a specific factor, explained a small part of said variance.